2005
DOI: 10.1099/mic.0.27265-0
|View full text |Cite
|
Sign up to set email alerts
|

The formation of cyclopropane fatty acids in Salmonella enterica serovar Typhimurium

Abstract: The formation of cyclopropane fatty acid (CFA) and its role in the acid shock response in Salmonella enterica serovar Typhimurium (S. typhimurium) was investigated. Data obtained by GC/MS demonstrated that the CFA level in S. typhimurium increased upon its entry to the stationary phase, as in other bacteria. The cfa gene encoding CFA synthase was cloned, and mutants of the cfa gene were constructed by allelic exchange. A cfa mutant could not produce CFA and was sensitive to low pH. Introduction of a functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
69
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 37 publications
4
69
0
2
Order By: Relevance
“…In Escherichia coli, a correlation between the level of CFAs in membrane and the resistance of the bacterium to a lethal pH was reported (6). The strategies, including the construction and the physiological study of cfa-deficient cells in E. coli (9) or Salmonella enterica serovar Typhimurium (33), likewise demonstrated the high sensitivity of the deficient cells to acid stress. An overexpression of the cfa gene in Clostridium acetobutylicum increased the CFA content of cells as well as acid and butanol resistance (47).…”
mentioning
confidence: 99%
“…In Escherichia coli, a correlation between the level of CFAs in membrane and the resistance of the bacterium to a lethal pH was reported (6). The strategies, including the construction and the physiological study of cfa-deficient cells in E. coli (9) or Salmonella enterica serovar Typhimurium (33), likewise demonstrated the high sensitivity of the deficient cells to acid stress. An overexpression of the cfa gene in Clostridium acetobutylicum increased the CFA content of cells as well as acid and butanol resistance (47).…”
mentioning
confidence: 99%
“…In some bacteria, exposure to acid leads to the up-regulation of the cfa gene (26,51), the product of which generates cyclopropanecontaining phospholipids. Exposure to acid leads to increased levels of these modified phospholipids (23,42), which are known to be important for acid stress resistance in Escherichia coli and Salmonella (30,60). Acid also can cause bacteria to up-regulate the F 1 F 0 ATPase (9,17,32,46), which can pump protons out of the cell at the expense of ATP.…”
mentioning
confidence: 99%
“…Bacteria can alter the composition of the membrane fatty acids by a number of processes, including cyclopropanation, cis-trans isomerization, (de)saturation, or the incorporation of free exogenous fatty acids into the membrane (7,9,18,21). It has been reported that bacterial membrane composition changes during acid shock (5,23), osmolarity fluctuations (46), freeze-drying (31), and exposure to suboptimal growth temperatures (16).…”
mentioning
confidence: 99%